PENGARUH NET PROFIT MARGIN, DER DAN ROE TERHADAP DIVIDENDPAYOUT RATIO PERUSAHAAN SUB SEKTORANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulya Rafika (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
From the preliminary research that the researchers conducted, dividend policy tends to be one of the most stable and predictable elements of firms, and most companies start paying dividends once they reach the maturity stage of business and when there are no more profitable investment opportunities for the company a percentage of the profits they earn will be paid to shareholders as cash dividend called the Dividend Payout Ratio. The purpose of this study was to determine whether the net profit margin, debt ro equity ratio and return on equity have an effect on the Dividend Payout Ratio in Miscellaneous Industry Sub-sector Companies Listed on the Indonesia Stock Exchange. The number of samples in this study amounted to 17 companies during the study period of 3 years so that the observational data were 51 samples. The analysis technique used is multiple linear regression. The results showed that the net profit margin had a significant effect on the dividend payout ratio. Debt to equity ratio has a significant effect on the dividend pay out ratio. Return on equity has no significant effect on the dividend pay out ratio. Taken together, the variables of net profit margin, debt-to-equity ratio and return on equity have a significant effect simultaneously on the dividend pay out ratio.